Closing the Gap in Access to Rural Communications : Chile 1995-2002 - Wellenius, Bjorn (Washington, DC: World Bank, 2013)
The study documents, and reviews the Chilean experience in rural telecommunications, by focusing on the principles, practical organization, basic design, and outstanding issues for extension of a more advanced form of approach to communication, and access to information. It examines in depth the results, and success factors of the Telecommunications Development Fund, established in 1994, a success largely due to the extensive reliance on market forces to determine, and allocate subsidies, to minimal regulatory intervention, and relatively simple processing. The design of the Fund proved robust, and remains the leading example of a cost-effective solution to reduce access gaps in basic communication in emerging economies. However, questions remain on the sustainability of services for the long run, on how to support the small, but still excluded rural population, and on potential, further needs in urban areas.